Effect of lipid-lowering therapies on flow-mediated dilation in patients: A systematic review and meta-analysis of clinical randomized controlled trials - Xinyue Wang; Lijun Zhou; Qiutao Wang; Min Wu (PLoS ONE, 2025)
Numerous lipid-lowering medications are commonly used in clinical settings; however, their impact on vascular endothelial function remains unclear. This study employed techniques like flow-mediated dilation (FMD) to demonstrate the relative effects of lipid-lowering medications on vascular function. PubMed, Embase, and World of Science were searched from January 1, 2011 to October 1, 2024, and the language was limited to English. Randomized controlled trials (RCTs) have assessed the impact of lipid-lowering medications versus placebos on FMD in individuals. The outcomes included FMD, pulse wave velocity (PWV), low-density lipoprotein cholesterol (LDL-C), peak O2 consumption (VO2), and intimal media thickness (IMT). We computed standardized mean differences and 95% confidence intervals (CIs). P < 0.05 indicates statistical significance. The quality of the RCTs was assessed according to the methods provided by the Cochrane Handbook, and effective data were extracted. Revman software 5.4 version was used for statistical analysis. Drug type, intervention duration, and underlying diseases were used as covariates in the subgroup analysis. This meta-analysis included 19 RCTs involving 1,004 patients. Compared with placebo, lipid-lowering agents significantly reduced FMD (0.20 [95% CI: 0.05, 0.35], P = 0.007, I2 = 43%, 14 trials, 726 participants), LDL-C (−1.54 [95% CI: −1.78, −1.30], P < 0.00001, I2 = 25%, 7 trials, 350 participants) and PWV (−0.35 [95% CI: −0.57, −0.02], P = 0.04, I2 = 0.0%, 4 trials, 206 participants). Lipid-lowering drugs positively affect endothelial function, while lowering blood lipids and statins are the most effective.